Influence of Nd and Er substitution on magnetic and dielectric properties of bismuth ferrite - Anuar, Amir (2014)
BiFeO3 (BFO) is one of the few multiferroic materials with ferroelectric and antiferromagnetic order at room temperature. It can be applied to many modern technologies, such as information storage and sensing devices. In general, BiFeO3 doped with rare earth elements can enhance the ferroelectric and ferromagnetic. In this thesis the structural changes, magnetic and dielectric properties of Nd and Er doped bismuth ferrite powders have been studied. BiFe1-nNdnO3 (n = 0.00, 0.10, 0.20, 0.30, 0.40) and BiFe1-nErnO3 (n = 0.00, 0.10, 0.20, 0.30, 0.40) were prepared by using conventional solid state method. The samples are then characterized by X-ray diffraction (XRD), EDX, VSM and impendence analyzer. The X-ray diffraction for Nd substituted BiFeO3 showed that the lattice constants and cell volume decreased with each substitution, and the crystal structure transformed from the R3c (hexagonal) to the R-3m (hexagonal) with the Nd content x increasing to 0.3. Hysteresis loop appear when the Nd is substituted for Fe showing ferromagnetic properties. Nd substitutions introduce the presence of uncompensated antiferromagnetic spin. At 100Hz in room temperature the pure bismuth ferrite dielectric permittivity is 26.281. When 0.1 Nd is substituted it increase to 33.079 and at 0.2 Nd substitutions it further increase to 38.75 when 0.2 Nd is substituted while at 0.3 and 0.4 the dielectric permittivity decrease to 23.082 and 17.682 respectively. When 0.3 of Nd is substituted the crystal structures change from R3c to R-3m which reduces the dielectric properties where R3c allow cooperative displacement of Fe3+ for polarization. X-ray diffraction showed that substitution of Er for Fe promotes the formation of Bi24Fe2O39 phase. When the Er content increases to 0.30, BiFeO3 structure transforms from R3c(hexagonal) to Bi24Fe2O39 I23(Cubic). The magnetic properties show improvement with every substitution especially at 0.3 where cubic crystal structure is easily magnetizes. Dielectric permittivity of Er doped BiFeO3 see a reduction with every substitution. The decline is associated with Bi24Fe2O39 which has a high leakage current is associated with it.